The dynamic elastic response to impulse synchronisation of composite prosthetic energy storing and returning feet. (March 2014) - Noroozi, Siamak; Rahman, Abdul GA; Khoo, Shin Y; Zahedi, Saeed; Sewell, Philip; Dyer, Bryce; Ong, Zhi C
In this research, it is proven that perfect synchronisation between the input impulse (human effort) and the ground reaction impulse/impact can result in a phenomenon called the dynamic elastic response to impulse synchronisation with favourable consequences to the behaviour of the energy storing and returning foot. An energy storing and returning composite prosthetic foot was first used in elite competition at the 1988 Paralympic Games. Since its introduction, the prostheses have proven to be a source of controversy. In 2008, it was concluded that the athletes who use such technology when running are in an advantageous position when compared to able-bodied athletes. However, these findings have since been disputed. There still remain unanswered questions regarding the level of contribution of energy storing and returning feet in the performance of amputee athletes. A series of investigations have previously been conducted to study the dynamic characteristics of a number of energy storing and returning composite prosthetic feet. It was found that if a sinusoidal input impulse, with a frequency close to one of the energy storing and returning feet's natural frequencies, could be applied, it can make the energy storing and returning foot susceptible to resonance, which, in the case of bending mode, if sustained can lead to a gain in height or increased velocity.